License and union fees in Peruvian legislation - Arévalo Vela, Javier (2019)
This article develops the regulation of the union license and fees as the rights of the leaders and of the trade union organization in the Consolidated Text of the Collective Labor Relations Act, as approved by Supreme Decree Nº 010-2003-TR, published in the Official Gazette El Peruano on October 5, 2003 (hereinafter TUOLRCT) and its regulations.